Mechatronic Wearable Exoskeletons for Bionic Bipedal Standing and Walking: A New Synthetic Approach - Onose, Gelu; Cârdei, Vladimir; Crăciunoiu, Ştefan T.; Avramescu, Valeriu; Opriş, Ioan; Lebedev, Mikhail A.; Constantinescu, Marian Vladimir (Frontiers in Neuroscience, 2016)
In the last few years, including nowadays, there is an important augmentation of the interest in the literature, on the subject matter of robotic type of portable/ wearable powered exoscheletons for bionic bipedal standing and walk assistance, including with the issue of the first related systematic literature reviews: thoroughly achieved and some of them expressly designed as evidence-based approaches. This is consistent with the technological progresses in the domain, so that the most advanced such devices has been subject for a series of recently accomplished – or pivotal, just initiated – studies, respectively single case reports or active clinical surveys on small number of enrolled subjects. Within the context above, this article intends to approach the field from a joint perspective: of professionals and – including, at the same time – of a consumer. It targets a taxonomic detailing attempt and respectively, to highlight the main necessary and feasible improvement directions, in order to contribute at hastening the reach of optimal – i.e. completely functional and accessible – model(s) of the respective kind of exoskeletons.